2007
DOI: 10.1021/ja071364v
|View full text |Cite
|
Sign up to set email alerts
|

VTVH-MCD and DFT Studies of Thiolate Bonding to {FeNO}7/{FeO2}8 Complexes of Isopenicillin N Synthase:  Substrate Determination of Oxidase versus Oxygenase Activity in Nonheme Fe Enzymes

Abstract: Isopenicillin N synthase (IPNS) is a unique mononuclear non-heme Fe enzyme that catalyzes the four electron oxidative double ring closure of its substrate ACV. A combination of spectroscopic techniques including EPR, absorbance, circular dichroism (CD), magnetic CD, and variabletemperature, variable-field MCD (VTVH-MCD) were used to evaluate the geometric and electronic structure of the {FeNO} 7 complex of IPNS coordinated with the ACV thiolate ligand. Density Function Theory (DFT) calculations correlated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
176
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(195 citation statements)
references
References 39 publications
15
176
2
Order By: Relevance
“…In the study on IPNS, Brown et al [162] This was done by Lundberg et al [167] who modeled the whole catalytic cycle of IPNS using the B3LYP/MM approach and calculated the free-energy barrier of HAA to be ~12 kcal mol -1 (the experimentally derived value is ~17 kcal mol general, a better oxidant than ferryl compounds and in fact its oxidation power strongly depends on the HAA reaction energy. Namely, they showed that for both types of oxidants, the HAA activation energies correlate well with reaction energies, thus obeying the BEP principle (see also section 3.2.5).…”
Section: Mononuclear Ferric-hydroperoxo Active Site: C─h + Hoo─fe IIImentioning
confidence: 99%
“…In the study on IPNS, Brown et al [162] This was done by Lundberg et al [167] who modeled the whole catalytic cycle of IPNS using the B3LYP/MM approach and calculated the free-energy barrier of HAA to be ~12 kcal mol -1 (the experimentally derived value is ~17 kcal mol general, a better oxidant than ferryl compounds and in fact its oxidation power strongly depends on the HAA reaction energy. Namely, they showed that for both types of oxidants, the HAA activation energies correlate well with reaction energies, thus obeying the BEP principle (see also section 3.2.5).…”
Section: Mononuclear Ferric-hydroperoxo Active Site: C─h + Hoo─fe IIImentioning
confidence: 99%
“…Spectroscopic studies highlight the role of charge donation from the ACV thiolate ligand that renders the formation of the ferric superoxo complex energetically more favorable. 22 The six unpaired electrons required to form the septet come from the parallel alignment of the unpaired spin on the superoxide with the spins from the unpaired electron on the superoxo must first flip, but this spin transition does not affect the rate of the reaction. 43 In the quintet spin state, the end-on structure ( 5 2 INT) is the most stable, and this structure is in good alignment to abstract hydrogen from the Cys β-carbon.…”
Section: Transition State For Cys-β-c-h Bond Activationmentioning
confidence: 99%
“…43 In the quintet spin state, the end-on structure ( 5 2 INT) is the most stable, and this structure is in good alignment to abstract hydrogen from the Cys β-carbon. 22 Compared to the active-site model, explicit inclusion of the protein mainly affects the position of the hydrophobic side chain of the valine and the orientation of the amino acid ligands, but has only small effects on the alignment of the reactive superoxide or the cysteine part of the substrate, see After probing the reaction coordinate using the C1-H1 and the O2-H1 distances, (see Figure 3 for labels) a transition state for C-H bond activation ( 5 3 TS) could be fully optimized in the "fully coupled macro/micro-iterative" optimization scheme. The same method, i.e., initial mapping of the reactive space using one or two reaction coordinates followed by full optimization, has been used for all transition states.…”
Section: Transition State For Cys-β-c-h Bond Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced oxygen then undergoes O-O bond cleavage to yield a molecule of water and leave an Fe(IV)=O species as in the 2-oxoacid dioxygenases or tetrahydropterin-linked hydroxylases. Finally, the high valent iron species is used as a reagent to complete a second part of the reaction, and in doing so, accepts two more electrons to form the second molecule of water.Some well-studied examples of 2-His+Asp/Glu oxidases are isopenicillin N-synthase (IPNS) [79][80][81] , fosfomycin synthase (FOS) 82,83 , and 1-aminocyclopropane-1-carboxylate oxidase (ACCO), which catalyzes the formation of ethylene, a hormone in plants [84][85][86] . These enzymes activate O 2 and ultimately form water using either 4 electrons from substrate (IPNS), two from substrate and two from NADH (FOS), or two from substrate and 2 from ascorbate (ACCO).…”
mentioning
confidence: 99%